Recurrent giant borderline phyllodes tumor: resection and breast reconstruction - MONTES-MADARIAGA, ELIZBET SUSAN; ORTIZ-SAAVEDRA, BRANDO; ALTAMIRANO-FARFAN, EULER; HERENCIA-ANAYA, MELISSA; PUMAMANGO-CORDOVA, JIMMY (Revista Brasileira de Cirurgia Plástica (RBCP) – Brazilian Journal of Plastic Surgery, 2024)
Phyllodes Tumor is a rare fibroepithelial neoplasm that represents 0.3 to 1% of all breast neoplasms. According to histopathologic classification, 12 to 26% are borderline type and approximately 15% of these tumors recur after surgical excision. The recommended treatment for all types of Phyllodes Tumor is surgical excision, and in the case of giant tumors, the treatment should be multidisciplinary. We present the case of a 46-year-old woman with a Phyllodes Tumor in the left breast that recurred 4 years after surgical excision. The anatomopathological study qualified it as a giant tumor and the histopathological study reported a Borderline Phyllodes Tumor. She underwent surgical excision with a left mastectomy and breast reconstruction employing a latissimus dorsi flap plus fat graft. The patient presented a favorable evolution without recurrence. In conclusion, the Recurrent Giant Borderline Phyllodes tumor is rare and its surgical management represents a challenge both in breast excision and reconstruction.
Keywords: Phyllodes Tumor; Mammaplasty; Surgical Flaps; Plastic Surgery Procedures; Mastectomy